PENGARUH MEMBACA CEPAT TERHADAP TINGKAT PEMAHAMAN BACAAN (Studi Kajian Literatur dan Penerapan bagi Mahasiswa STKIP Muhammadiyah Muara Bungo) - YULIA OKTARINA SUBHANADRI (Inovasi Pendidikan, 2017)
The purpose of this research was to analyze and describe the effect of fast reading on the level of comprehension of reading content as a study of literature review and application for students of PGSD Study Program STKIP Muhammadiyah Muara Bungo. This research has achieved some of its output targets. It was used as material in the local scientific meeting that has been held in STKIP-MB. The results of this study will be published in the National Journal of ISSN. This research used quantitative approach with quasi experiment and descriptive research. This research was conducted on students of STKIP MB Academic Year 2016/2017. The conclusions of this research were: (1) the study of literature review indicated that fast reading could give positive effect to reading comprehension level. The application of fast reading should consider the types of reading, reading objectives, and discourse readability levels, (2) the reading comprehension level after applying fast reading was better than the reading comprehension level before applying the fast reading when the researcher was done on same research subjects, (3) the reading comprehension level by applying fast reading was better than the reading comprehension level by applying conventional reading when the researcher was done on different research subjects. Thus, fast reading affects the level of reading comprehension, both in analyzing the study of literature review and on application for students of STKIP Muhammadiyah Muara Bungo.Keywords: fast reading, reading comprehension level